Combined foliar application of calcium, zinc, boron and time influence leaf nutrient status, vegetative growth, fruit yield, fruit biochemical and anti-oxidative attributes of "Chandler" strawberry. (21st July 2022) - Salman, M.; Ullah, Sami; Razzaq, Kashif; Rajwana, Ishtiaq A.; Akhtar, Gulzar; Faried, Hafiz Nazar; Hussain, Abid; Amin, M.; Khalid, Samina
Abstract: The aim of this research was to evaluate the effect of foliar application of calcium (Ca), Boron (B) and Zinc (Zn) alone and in combination along with different times of application (pre-flowering stage, post fruit development and combined application at both stages) on the plant growth, yield and quality of strawberry fruit. Foliar application of Ca alone and combined with Zn and B were applied. The experiment was arranged under randomized complete block design in split plot arrangement. Irrespective to application time, strawberry plant sprayed with combined application of Ca, Zn and B exhibited significantly increased leaf macro-nutrients (N, P, K, Ca), micro-nutrients (Zn, B, Fe), average fruit weight, yield, fruit size, fruit firmness, significantly higher TSS:TA ratio, ascorbic acid contents, anthocyanin and also antioxidative enzymes activity viz. catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD)] than untreated plants. Similarly, spraying at both stages (pre-flowering and post-fruit development) significantly increased number of leaves, fruits, yield and average fruit weight, significantly higher fruit TSS:TA ratio, vitamin C, anthocyanin and also anti-oxidative enzymes viz. CAT, SOD and POD of strawberry fruit. In conclusion combined foliar application of Zn, B and Ca applied at pre-flowering stage and post fruit development significantly improved the vegetative growth, fruit yield, fruit bio-chemical attributes and antioxidative enzymes attributes.